POST-TRADISIONALISME PESANTREN; MENGUKUHKAN TRADISI PESANTREN SEBAGAI BASIS TRANSFORMASI DI ERA MODERN - Hamam Burhanuddin (AL-MURABBI: Jurnal Studi Kependidikan dan Keislaman, 2014)
Pesantren was the representation of Islam education original Indonesia (indigenous) that now still exists and could maintain his existence in the middle of the global arena in the educational agency, Pesantrent previously was known with classic education apparently to be conservative, dirty and backward with education modern. It term that now be proper for must be reviewed. Studied about the social function of Pesantren was needed with weighed repeated the role and the dynamics of pesantren in the Indonesian community modern, where the dynamics of the modernity influenced the existence of pesantren fundamentally so as to result in the problem emergence of the cultural identity of pesantren. This problem could be regarded as the consequences and the logical implications when being connected with the modernity that had the obligation that influenced specially the social function and the culture that were provided a basis for on the religious obligation. The study in this article focused to the side of how far pesantren could as the Islam religious institution strengthen the tradition and made him the basis of the transformation in the modern era. In the capacity whether Pesantren could play social functions of the culture in the student's community in the middle of the modernity in the Indonesia community